Preparation and enhanced electrocatalytic activity of graphene supported palladium nanoparticles with multi-edges and corners. Issue 101 (17th October 2016) - Liu, Zhelin; Feng, Yinghui; Wu, Xiaofeng; Huang, Keke; Feng, Shouhua; Dong, Xiangting; Yang, Ying; Zhao, Bo
Abstract : Pd nanoparticles with multi-edges and corners are prepared and assembled on reduced graphene oxide to examine the electrocatalytic activity. Point discharge is regarded to be capable of facilitating the electron transfer. Abstract : Herein, we reported a facile and green synthesis of palladium nanoparticles with a concave and convex surface formed by multi-edges and corners only involving palladium precursor and ascorbic acid. Ascorbic acid was employed as both reductant and structure-directing agent. The as-prepared palladium nanoparticles were then assembled on reduced graphene oxide. The morphology and chemical composition of the products were confirmed by several characterization techniques. The fast development of fuel cells inspired us to examine the electrocatalytic activity of the products towards methanol, ethanol and formic acid electrooxidation in alkaline medium comparing with that of the commercial one. The characterization and electrochemical results were carefully analyzed and discussed, showing the product can be applied as a well-performed electrocatalyst towards the electrooxidation of methanol, ethanol, and formic acid in alkaline media. The possible electron transfer route was proposed with the assistance of MedeA VASP calculation.